2021
DOI: 10.48550/arxiv.2102.13646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generating high-order quantum exceptional points in synthetic dimensions

Ievgen I. Arkhipov,
Fabrizio Minganti,
Adam Miranowicz
et al.

Abstract: Recently, there has been intense research in proposing and developing various methods for constructing high-order exceptional points (EPs) in dissipative systems. These EPs can possess a number of intriguing properties related to, e.g., chiral transport and enhanced sensitivity. Proposals to realize high-order EPs have been based on the use of non-Hermitian Hamiltonians (NHHs) of composite systems, i.e., the operators describing the evolution of coupled post-selected systems or coupled intense light fields. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Therefore, it is very important to investigate this question and we plan to do so in near future. Note that the studies on Liouvillian exceptional points have been actively conducted recently [16,17,42,45,46]. Also, as a natural extension, we may consider application of the third quantization to an open 2N -spin model which has alternately pumping spins along opposite directions.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is very important to investigate this question and we plan to do so in near future. Note that the studies on Liouvillian exceptional points have been actively conducted recently [16,17,42,45,46]. Also, as a natural extension, we may consider application of the third quantization to an open 2N -spin model which has alternately pumping spins along opposite directions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Similar discussions have been conducted and it has been shown that there are infinite order Liouvillian exceptional points for other quadratic bosonic models in Refs. [42,45,46]. Also, it is known that at an exceptional point, the eigenspace cannot be spanned only by the eigenstates, but generalized eigenstates are required [40].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation